2015
DOI: 10.1007/s10802-015-0099-3
|View full text |Cite
|
Sign up to set email alerts
|

Early Callous-Unemotional Behavior, Theory-of-Mind, and a Fearful/Inhibited Temperament Predict Externalizing Problems in Middle and Late Childhood

Abstract: Childhood externalizing problems are more likely to be severe and persistent when combined with high levels of callous-unemotional (CU) behavior. A handful of recent studies have shown that CU behavior can also be reliably measured in the early preschool years, which may help to identify young children who are less likely to desist from early externalizing behaviors. The current study extends previous literature by examining the role of CU behavior in very early childhood in the prediction of externalizing pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 67 publications
3
27
1
2
Order By: Relevance
“…Related to this distinction, previous research has shown intact cognitive perspective-taking abilities (theory of mind) but impairments in affective empathy (responsivity to others' distress) in children with CU symptoms (e.g., Jones, Happé, Gilbert, Burnett, & Viding, 2010). Possibly reflecting a similar dissociation between cognitive and affective empathy, the current results showed a positive correlation between mentalizing and CU traits, although the interpretation of this unexpected result (see Song, Waller, Hyde, & Olson, 2016) remains unclear.…”
Section: Discussioncontrasting
confidence: 42%
“…Related to this distinction, previous research has shown intact cognitive perspective-taking abilities (theory of mind) but impairments in affective empathy (responsivity to others' distress) in children with CU symptoms (e.g., Jones, Happé, Gilbert, Burnett, & Viding, 2010). Possibly reflecting a similar dissociation between cognitive and affective empathy, the current results showed a positive correlation between mentalizing and CU traits, although the interpretation of this unexpected result (see Song, Waller, Hyde, & Olson, 2016) remains unclear.…”
Section: Discussioncontrasting
confidence: 42%
“…CU behaviors were assessed using a five-item measure (“shows lack of guilt after misbehavior”, “seems unresponsive to affection”, “shows too little fear”, “punishment doesn’t change behavior” and “shows a lack of affection to others”), previously shown to factor separately from other dimensions of externalizing behavior (i.e., oppositional and attention-deficit behaviors) in five independent samples of children during the age period from 2–4 years old, including in the current sample (Kimonis, Bagner, Linares, Blake, & Rodriguez, 2014; Waller, Hyde et al, 2015; Waller, Shaw et al, 2015; Willoughby, Waschbusch, Moore, & Propper, 2011; Willoughby, Mills-Koonce, Gottfredson, & Wagner, 2014). Moreover, in support of its construct and predictive validity, CU behaviors as measured with these items have been uniquely related to lower parent-reported moral regulation, empathy, and guilt (Waller, Hyde et al, 2015), and predicted more teacher-reported externalizing problems at ages 6 (Waller, Hyde et al, 2015) and 10 (Song, Waller, Hyde, & Olson, 2015) within the current sample. To create a valid cross-informant measure of early CU behaviors, we computed the mean of items across mother and father reports ( r =.35, p <.01; combined measure, α=.66).…”
Section: Methodsmentioning
confidence: 55%
“…In addition, the five-item CU behaviors measure used items that were not originally developed to assess the CU construct. Although its predictive and construct validity has been supported by previous studies in the current sample (Song et al, 2015; Waller, Hyde et al, 2015), future studies are needed that examine interactions between early childhood CU behaviors and executive function deficits using “purpose-developed” measures, such as the Inventory of Callous-Unemotional Traits (Frick, 2004). Moreover, although one study to date has examined the stability of CU behaviors from early to late childhood (Waller et al, 2016), more evidence is needed to confirm the homotypic continuity of the CU construct across childhood.…”
Section: Discussionmentioning
confidence: 82%
“…Other psychological and psychiatric disorder in which there could be an impairment or dysfunctions in mentalization ability or ToM are for example ADHD ( 18 , 19 ), intellectual disability ( 20 ), externalizing disorders, also connected with high levels of callous-unemotional (CU) traits ( 21 ) and, especially regarding metacognition and metacognitive strategies, learning disabilities ( 22 ).…”
Section: Introductionmentioning
confidence: 99%